Correlation of Pre-Operative Myo-Inositol/Creatine Ratio with Histopathological Grade of Glioma (Bangladesh Journal of Neurosurgery, 2024)
Background: Introduction: Gliomas are the most frequent primary intracerebral tumors in adults & constitute 35–50% of all intracranial neoplasms. In determining a treatment plan, tumor grade is a key consideration for minimizing the risk of unnecessary morbidity and mortality. Objective: To evaluate Correlation of pre-operative Myo-inositol/Creatine ratio with histopathological grade of glioma. Materials and method: This was a cross sectional experimental study. Total 33 patients consistent with selection criteria were enrolled in this study. Myo-inositol/ Creatine ratio was obtained from MRS. Histopathological grade of glioma was obtained from biopsy (hematoxylin and eosin stain or HE stain) report. The obtained results were then grouped categorically. Result: Out of 33 patients, 22 were male and 11 were female. According to histopathology, 14 gliomas were confirmed as high grade and 19 gliomas were confirmed as low grade. Spearman Rank Correlation Test showed a moderate negative association between Myo-inositol/Creatine ratio with glioma grading with coefficient value of r = -0.611 with a statistically significant p-value (p